“O natal do viúvo” – or the paralyzed body - Garcia, Cristiane de Oliveira Fernandes (Literatura e Sociedade, 2010)
Among the dilemmas experienced by contemporary Brazilian literature, especially over the last two decades of the twentieth century, I have chosen to discuss issues of identity and subjectivity, as they present themselves in the short story by Modesto Carone “O natal do viúvo”. This study aims to investigate the aesthetic formalization of social issues present in Modesto Carone`s and hopes to contribute to new possibilities of interpretating the Brazilian author’s work within the reality of contemporary literature, understood as a critical element of society.